Failure prediction of ship windows subjected to wave impacts. Issue 3 (October 2015) - Gerlach, B.; Fricke, W.; Guiard, M.; Ferreira González, D.; Abdel-Maksoud, M.
Abstract : Window failure due to wave impact was reported several times in the recent past; some incidents had severe consequences, including the loss of life. The event is extremely complex. Experimental investigations, complemented by finite element and hydrodynamic analyses, give a more comprehensive understanding on the prevailing phenomena. In this paper, experiments that were conducted by drop tests with water-filled rubber bags on a test wall, containing a window, are presented. This paper also describes the numerical model used to simulate the experiments, which consists of finite elements and smoothed particles. Calculated results are then compared with measurements. Thereafter, a method to simulate wave impacts on ship structures to determine the failure probability of the affected windows is developed. As an example, the method is applied to windows in the front bulkhead of an offshore jack-up vessel.